An improved method for deleting large regions of Escherichia coli K-12 chromosome using a combination of Cre/loxP and Red - Fukiya, S.; Mizoguchi, H.; Mori, H.
We have established an improved large deletion method in Escherichia coli genome using a combination of two different recombination systems, Red and Cre/loxP. The loxP site could be rapidly and efficiently integrated in the genome by Red and large deletions of both 117- and 165-kbp regions could be generated in 100
Keywords: ESCHERICHIA COLI; GENOME ENGINEERING; CRE/LOXP; RED; LARGE DELETION